TCP Performance Measurement in Different GPRS Network Scenarios - Othman, A.K.; Zakaria, M.; K., Ab. Hamid (IEEE, 2007)
This paper presents the results of measured TCP performance in one of the commercially deployed live GPRS network in Malaysia under various network scenarios based on userspsila physical locations. End-to-end evaluation of FTP application is used for the assessment. Tracing at the GPRS air interface is done simultaneously, using a proprietary GSM/GPRS air interface testing tool and software. The results show that TCP performance is stable in all scenarios and can adapt fairly well to GPRS mobility and bad channel condition, although at the expense of reduced throughput. TCP imposes its slow start/congestion avoidance mechanism in such situations where packet loss is common. Tuning the TCP parameters to optimise its performance also proves to be beneficial.